Hypokalemia Caused by Quetiapine and Risperidone Treatment in Schizophrenia: A Case Report. Issue 3 (25th July 2018) - Yang, Qiongwei; Guo, Xiaoyun; Liu, Dengtang
Abstract : Hypokalemia can cause abnormalities in multiple systems. Long term use of antipsychotic medications can lead to electrolyte imbalance, including hypokalemia. We report a 49-year-old female patient with schizophrenia who developed hypokalemia after oral quetiapine and risperidone treatments. Her blood potassium became normal after she switched to another antipsychotic drug (amisulpride). In addition, we discuss the potential mechanism of antipsychotic drugs leading to hypokalemia and clinical cautions.